COMPARATIVE ASSESSMENT OF METHODS OF INCLUDED DENTITION DEFECTS REPLACEMENT IN PATIENTS WITH STAGE I GENERALIZED PERIODONTITIS - Popovych, I.Y.; Petrushanko, T.O.; Petrushanko, V.M. (World of Medicine and Biology, 2024)
Several ways exist to restore the missing teeth in the presence of included defects. These include implantation, removable prosthetics and the manufacturing of dental bridges. The purpose of the study was to perform a comparative characterization of various restoration methods of the tooth row, including defects in patients with stage I generalized periodontitis. 61 patients with subsequent replacement of the dentition defect were examined, namely, 19 patients, with the help of removable structures. In 20 patients, dental implants were used, and in 22 patients, fixed dental bridges were made to replace the defect. The condition of the abutment teeth was assessed before the restoration, after 6, 12 and 24 months. The study's results (the amount of epithelial attachment loss, periotestometry data, and the level of bone tissue resorption) testify to the advantages of using dental implants to replace included dentition defects. Installing dental implants creates conditions for a uniform chewing load, which promotes stable remission and stabilization of the inflammatory and dystrophic process in periodontal tissues, creates comfort for the patient and improves his quality of life.
Keywords: dentition defect; generalized periodontitis; dental implantation; tooth mobility; tooth restoration